TENTIYO SUHARTO Konsep Syirkah (Musyarakah) Dalam Tafsir Ibnu Katsir Telaah Al-Qur’an Surah Shaad Ayat 24 Pada Lembaga Keuangan Syariah - Suharto Tentiyo (Program Studi Perbankan Syariah Jurusan Syariah, Ekonomi dan Bisnis Islam Sekolah Tinggi Agama Islam Negeri Mandailing Natal (STAIN MADINA), 2022)
Abstract Syirkah, also known as musharaka, is a business partnership that is jointly owned by two or more people. Types of Syirkah, Syirkah al 'Inan. Syirkah al Mufawadlah, Syirkah al A'maal. Based on the understanding of the interpretation of al-syirkah according to Ibn Kathir, it can be concluded that it is a transaction between two or more people. This transaction includes the collection of capital and the use of capital. Profits and losses are shared according to the agreement. However, capital is not always in the form of money but can take other forms. By ijma, the scholars agree that the law of shirkah is permissible. Based on the hadith that Allah's recommendation is to cooperate without betrayal and Allah's threat to those who enter into an alliance in which there is betrayal between the two parties. Sharia Financial Institutions in taking advantage of developing the principle of profit sharing. One of them is using the principle of syirkah. Syirkah is a cooperation contract between two or more parties for a particular business in which each party contributes (charity and expertise) with an agreement that the profits and risks will be shared according to the agreement. In the practice of sharia banking, this syirkah principle has become the prima donna, in terms of financing. Keywords: Shirkah. Musyarakah, Tafsir, Capital, Transactions, Hadith, Sharia, Law, Cooperation, Economics, Contributions, Trade, Transactions, Loss.